Investigation on the Effect of Charge Carriers in Chemical Shift Anisotropy of Si Single Crystal. Issue 1 (April 2021) - Viswanathan, E.; Padma Prasad, K.; Ganapathy, S.
Abstract: The Chemical Shift Anisotropy (CSA) of single crystalline silicon (Si) was investigated using 29 Si static NMR for commercially procured p-type and n -type silicon. The observed CSA has been distributed between -80 ppm to -90 ppm for n- type and p -type Si. The NMR parameters such as Isotropic Chemical Shift (5iso ), Chemical Shift Anisotropy tensor (ΔS) and the asymmetry parameter (77 ) of the CSA were extracted by using DMFIT with the CSA-static model. The ΔS and rj are found to be - 1.73 ppm and 0.3 ppm respectively for the n -type and the asymmetry parameter of the CSA was found one order different from p -type material. The changes observed in CSA pattern and spin-lattice relaxation ( T 1 ) time are ascribed to strength (mobility) of the shallow donor level and shallow acceptor level effects in the Fermi contact term.